Cold War in the Desert - Kelly, S. author. aut Link
IX, 207 p.
Keywords: The question of the Italian colonies played an important part in the breakdown of Allied cooperation after the Second World War. Britain and the United States were closely involved in this question, yet their respective roles have not received the detailed historical attention which they merit. Based on extensive research in British and American archives, this book will seek to analyse British and US policy on this question within its Cold War context.